IMPLEMENTASI PERATURAN DAERAH NOMOR 1 TAHUN 2013 TENTANG TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN - Ade Hendri Alamsyah (Universitas Riau, 2016)
Implementation of Regional Regulation Number 1 Year 2013 About Social and Environmental Responsibility. This study aims to determine the implementation Siak District Regulation Number 1 Year 2013 About Corporate Social Responsibility and Environment in Siak and obstacles encountered in implementing Siak District Regulation Number 1 Year 2013 About Corporate Social Responsibility in Siak. This type of research is the use descriptive research. While the research informants include officials and employee who is on BAPPEDA Siak involved as the Forum of Corporate Social Responsibility (CSR) Siak, the company chosen by the researchers BOB PT. Bumi Siak Pusako and communities. Analysis of the data obtained were analyzed from data presentation, data reduction, verification and conclusion. Implementation of Regional Regulation Number 1 Year 2013 About Social and Environmental Responsibility in Siak materialized with the establishment of a forum with the CSR Forum Siak in order to realize corporate social responsibility for the community and also responsibility towards environmental integrity of the company’s operations in the region. Tanggaung environmental and social responsibility undertaken by each company in Siak district, is part of the company’s participation in the construction melaksanan Siak Regency. Obstacles to be a factor in creating effective policies encountered in the research and discussion, it is known is, the lack of availability of technical personnel.